Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.jafc.2c04624
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer-Specific Study of Fenpropathrin in Soil-Earthworm Microcosms: Enantioselective Bioactivity, Bioaccumulation, and Toxicity

Abstract: In this study, the enantiomer-specific bioactivity, bioaccumulation, and toxicity of fenpropathrin (FEN) enantiomers were investigated in soil-earthworm microcosms. The bioactivity order was S-FEN > rac-FEN > R-FEN for Spodoptera litura and Conogethes punctiferalis. Moreover, S-FEN was 12.0 and 32.2 times more toxic than rac-FEN and R-FEN to earthworms, respectively. S-FEN degraded faster than R-FEN with the enrichment of R-FEN in the soil environment. Furthermore, the peak-shaped accumulation curves for FEN e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…9 As for FEN, a previous study has revealed that the bioactivity of S-FEN is 7.9 and 18.3 times higher than that of R-FEN against Spodoptera litura and Conogethes punctiferalis, respectively. 10 However, few studies have yet been conducted to investigate the different bioactivity of FEN enantiomers against T. cinnabarinus as well as the mechanism underlying enantiomer-specific toxicity in T. cinnabarinus at the enantiomer metabolism level, therefore studying the bioactivity and metabolic differences of FEN enantiomers in T. cinnabarinus will help us understand the enantiomer-specific toxicity mechanism of chiral acaricides in leaf mites.…”
Section: Introductionmentioning
confidence: 99%
“…9 As for FEN, a previous study has revealed that the bioactivity of S-FEN is 7.9 and 18.3 times higher than that of R-FEN against Spodoptera litura and Conogethes punctiferalis, respectively. 10 However, few studies have yet been conducted to investigate the different bioactivity of FEN enantiomers against T. cinnabarinus as well as the mechanism underlying enantiomer-specific toxicity in T. cinnabarinus at the enantiomer metabolism level, therefore studying the bioactivity and metabolic differences of FEN enantiomers in T. cinnabarinus will help us understand the enantiomer-specific toxicity mechanism of chiral acaricides in leaf mites.…”
Section: Introductionmentioning
confidence: 99%